Parental Overprotection and Young Adults’ Autonomy: The Mediating Role of Self-Efficacy - Motevalli, Saeid; Marjan Baniasadi, Tayebeh (Journal of Psychosociological Research in Family and Culture, 2025)
Objective: This study aimed to examine the mediating role of self-efficacy in the relationship between perceived parental overprotection and autonomy in Malaysian young adults.Methods and Materials: A descriptive correlational research design was employed involving a sample of 423 university students in Malaysia, selected based on Krejcie and Morgan’s sampling table. Participants completed standardized measures including the Parental Bonding Instrument (Overprotection subscale), General Self-Efficacy Scale, and the Autonomous Functioning Scale. Data were analyzed using SPSS-27 for descriptive statistics and Pearson correlations, and AMOS-21 for structural equation modeling (SEM). Assumptions such as normality, multicollinearity, and linearity were checked and confirmed before inferential analysis.Findings: The results indicated a significant negative correlation between parental overprotection and autonomy (r = –.47, p < .001), and between parental overprotection and self-efficacy (r = –.41, p < .001). Self-efficacy was positively correlated with autonomy (r = .53, p < .001). SEM results showed that parental overprotection significantly predicted lower self-efficacy (β = –0.41, p < .001) and autonomy both directly (β = –0.28, p < .001) and indirectly via self-efficacy (β = –0.22, p < .001). The total effect of parental overprotection on autonomy was substantial (β = –0.50, p < .001). Model fit indices supported the adequacy of the hypothesized model (χ²/df = 1.74; CFI = 0.96; RMSEA = 0.041).Conclusion: These findings suggest that parental overprotection has a significant negative impact on young adults’ autonomy, both directly and through its detrimental effect on self-efficacy. Promoting self-efficacy may help mitigate the negative developmental consequences of overprotective parenting, especially in collectivist cultures where parental control is often normative.